Respiration-entrained brain rhythms are global but often overlooked - Tort, Adriano B. L.; Brankačk, Jurij; Draguhn, Andreas (Trends in neurosciences, 2018)
We revisit recent evidence showing that nasal respiration entrains oscillations at the same frequency as breathing in several regions of the rodent brain. Moreover, respiration modulates the amplitude of a specific gamma sub-band (70-120Hz), most prominently in frontal regions. Since rodents often breathe at delta and theta frequencies, we caution that previous studies on delta and theta power and their cross-regional synchrony, as well as on delta-gamma and theta-gamma coupling, may have detected the respiration-entrained rhythm and respiration-gamma coupling. We argue that the simultaneous tracking of respiration along with electrophysiological recordings is necessary to properly identify brain oscillations. We hypothesize that respiration-entrained oscillations aid long-range communication in the brain.
Gesehen am 16.04.2019